Podłoże genetyczne czerniaka złośliwego błony naczyniowej oka - Proniewska-Skrętek, Ewa; Wojnar, Małgorzata; Mariak, Zofia; Zalewska, Renata (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Genetic mechanisms underlying formation of ocular and skin melanoma differ in many aspects, the former being still poorly understood. It has been suggested that chorioidal melanoma can develop due to accumulation of genetic alterations in the DNA of normal melanocytes. Neoplasmatic transformation in the chorioidea can be triggered as a consequence of the following genetic alterations: – deletions and/or amplifications in the genetic material, usually in the chromosome 3, 6, 8, 9, 11, and 18; – point mutations, especially within some egzones, which leads to monosomia or loss of heterozygosity of the chromosome. As a consequence of the above alterations a number of false codons can appear resulting in formation of defective enzymatic proteins. Some of these proteins, like p16 and p14, normally play a role of supressors of oncogenesis and defects in their structure may result in melanoma formation.